Effects of dietary clinoptilolite and calcium levels on uric acid and calcium blood concentrations and bone quality of commercial layers - Berto, Dirlei Antonio [UNESP]; Garcia, Edivaldo Antonio [UNESP]; Vercese, F. [UNESP]; dos Santos, G. C. [UNESP]; Barreiro, F. R. [UNESP]; de Molino, A. B. [UNESP]; Pelícia, K.; da Silveira, A. F. [UNESP] (FapUNIFESP (SciELO), 2013)
The objective of the present study was to evaluate the effect of clinoptilolite and calcium levels on uric acid and calcium blood profile and bone quality of commercial layers. A total of 576 birds were distributed according to a completely randomized experimental design in a 3×4 factorial arrangement (calcium levels of 2.5, 3.1, or 3.7% and clinoptilolite levels of 0.0, 0.15, 0.25, or 0.50%), into 12 treatments with six replicates of eight birds per cage (experimental unit). The experimental period was 112 days. The experimental diets were based on corn and soybean meal. Results were submitted to analysis of variance and means were compared by the test of Tukey at 5% significance level using SISVAR statistical package. Blood uric acid was significantly influenced by the interaction of the evaluated factors. Clinoptilolite levels significantly increased blood calcium levels. There was no effect of dietary calcium levels on any of the evaluated characteristics. It was concluded that feeding layers with up to 0.50% clinoptilolite does not benefit blood uric acid and calcium concentrations and does not affect their bone quality. When layers at the end of the first laying cycle are fed ad libitum and present 119.50g/hen/day average feed intake, 3.1% dietary calcium promotes 3.7g/hen/day calcium intake, which is sufficient to maintain adequate calcium blood levels and bone quality.
Keywords: Bone quality; Mineral homeostasis; Zeolite